1981
DOI: 10.1002/pros.2990020208
|View full text |Cite
|
Sign up to set email alerts
|

The use of serum isoenzymes of alkaline and acid phosphatase as possible quantitative markers of tumor load in prostate cancer

Abstract: The tumor burden of 98 patients with metastatic prostatic cancer was compared longitudinally with the activities of bone (BAP) and liver isoenzymes (LAP) of alkaline phosphatase, total acid phosphatase (AcP), and prostate-specific acid phosphatase (PAP). A quantitative association between these enzyme markers and the tumor mass was suggested by comparing the enzymes with 1) both the treatment response and the estimation of metastasis by radionuclide bone scanning; 2) metastasis based upon radiographic evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…reports have emerged from Europe and the United States (Killian et al 1981;Pollen et al 1984). Osteoblastic metastatic tumors in prostate and breast cancer are the most common tumor types, and flare phenomena in lung cancer have been reported on 7 occasions (Cosolo et al 1988;Lemieux et al 2002;Arai and Kojima 2007;Chao et al 2009;Krupitskaya et al 2009;Lind et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…reports have emerged from Europe and the United States (Killian et al 1981;Pollen et al 1984). Osteoblastic metastatic tumors in prostate and breast cancer are the most common tumor types, and flare phenomena in lung cancer have been reported on 7 occasions (Cosolo et al 1988;Lemieux et al 2002;Arai and Kojima 2007;Chao et al 2009;Krupitskaya et al 2009;Lind et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…These changes are called 'flare phenomenon' and were first reported by Greenberg et al (1972). Flare phenomenon has been reported for prostate cancer and breast cancer, as well as gastroenterological and lung cancers (Killian et al 1981;Cosolo et al 1988;Vogel et al 1995;Amaroso et al 2007). Unfortunately, the clinical significance and mechanisms underlying the flare phenomenon remain poorly understood.…”
mentioning
confidence: 95%
“…NPCP criteria of clinical response were then utilized [1][2][3][4][5][6][9][10][11][12]. Bone scans were classified as 0, M 0 > no lesions; 1, M 1 = 0-6 lesions; 2, M 2 > 6-20 lesions; 3, M 3 > 20 lesions; and 4, M 4 = SuperScan [3].…”
Section: Methodsmentioning
confidence: 99%
“…In fact, based on these efforts a satisfactory semiquantitative method for assessing the extent of disease in such patients was developed [3]. At the same time, the NPCP was also evaluating the possibility that a quantitative association could be estimated between tumor extent and response to therapy, as judged by serial serum bone alkaline phosphatase activity [4]. Early results available at the time suggested that bone alkaline phosphatase activity, compared to total alkaline phosphatase activity, could be useful for initial and follow-up evaluation of such patients [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation